Digital Activism Rancangan Undang – Undang Tindak Pidana Kekerasan Seksual : (Analisis Jaringan Komunikasi terkait isu RUU TPKS di Twitter) - Ramadhani, Alif; Arianto, Irwan Dwi (Jurnal PIKMA : Publikasi Ilmu Komunikasi Media Dan Cinema, 2022)
Cases of sexual violence that appeared continuously in December 2021, increased the discussion on Twitter regarding the issue of the ratification of the Draft Law on the Crime of Sexual Violence.The high level of discussion gave rise to digital activism in the form of encouragement and pressure to ratify the RUU TPKS. But on the other hand, the urgency of sexual violence that emerged during the discussion of the RUU TPKS did not make all parties agree with the digital activism movement to ratify the RUU TPKS. These differences generate debates to form a communication network. The network formed consists of clusters consisting of actors involved in it. This study aims to map the communication network that is formed on the issue of the RUU TPKS, using the keyword "RUU TPKS". The analysis in this network is based on the analysis of Eriyanto's communication network, and strengthened by the level of analysis of Suratnoaji & Arianto, namely the level of content, behavior, and network analysis. This study shows that the discussion of the RUU TPKS increased on December 8, 2021, and was quite volatile until January 18, 2022. The results showed that there were 15,159 vertices, and 33,308 edges formed. An important actor in the RUU TPKS network in controlling the spread of information is @dpr_ri. This is based on the fact that the actor has a high centrality in several aspects of the assessment. The direction of opinion formed in the RUU TPKS network is dominated by positive sentiment, meaning that the public fully supports the ratification of the RUU TPKS. In addition, the cohesiveness of the supporting clusters shows a higher value than the repellent clusters in the network formed.